2021
DOI: 10.1063/5.0077549
|View full text |Cite
|
Sign up to set email alerts
|

Negligible rate enhancement from reported cooperative vibrational strong coupling catalysis

Abstract: We report the results of an attempt to reproduce a reported cavity catalysis of the ester hydrolysis of para- nitrophenyl acetate due to vibrational strong coupling. While we achieved the same light–matter coupling strength and detuning, we did not observe the reported ten-fold increase in the reaction rate constant. Furthermore, no obvious detuning dependence was observed. The inconsistency with the reported literature suggests that cavity catalysis is sensitive to experimental details beyond the onset of vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 53 publications
3
68
1
Order By: Relevance
“…In the conventional approach concentrating on the cavity induced modification of the individual reaction rates within the transition state theory, it is found that all the polaritonic effects should disappear when the number of molecules forming the polariton is increased [20][21][22][23]. Furthermore, very recently, there have been reports of failed replication experiments [24,25], adding to the confusion.…”
mentioning
confidence: 99%
“…In the conventional approach concentrating on the cavity induced modification of the individual reaction rates within the transition state theory, it is found that all the polaritonic effects should disappear when the number of molecules forming the polariton is increased [20][21][22][23]. Furthermore, very recently, there have been reports of failed replication experiments [24,25], adding to the confusion.…”
mentioning
confidence: 99%
“…. (11) In Eq. 10, δ L and δ R are the average (dimensionless) energy loss from the unstable mode when the system returns to the barrier, associated with the left and right wells, respectively, and can be obtained from [39]…”
Section: B Rate Theorymentioning
confidence: 99%
“…A series of recent experiments [1][2][3][4][5][6][7][8] have demonstrated that chemical kinetics can be enhanced [4,6,8] or suppressed [1,5], molecular bonds can be selectively broken [2], and selective crystallization can be achieved [9] via the formation of vibrational polaritons. On the other hand, several studies [10,11] have also reported possible discrepancies or inconsistencies in the interpretation of experiment purporting sizable kinetic effects. Thus, a rigorous theoretical understanding of the range of possible cavity-induced modifications to chemical kinetics is actively sought.…”
Section: Introductionmentioning
confidence: 99%
“…A possible way to circumvent these two obstacles is to tune the frequencies of an optical cavity to selectively alter the ground state chemical reactivity of molecules, which was demonstrated recently experimentally. [1][2][3] This research avenue has attracted many experimental, [4][5][6][7] computational, [8][9][10][11][12][13][14][15][16] and theoretical [17][18][19][20] investigations in recent years as which reactions can be manipulated by optical cavities and the underlying mechanism of how cavities can modify chemical reactivity are still an open questions. [21][22][23] In this work, we study the reaction rate inside an optical cavity by developing a non-Markovian dynamical model.…”
Section: Introductionmentioning
confidence: 99%